2014
DOI: 10.1186/preaccept-6892873451261068
|View full text |Cite
|
Sign up to set email alerts
|

The neutralizing function of the anti-HTLV-1 antibody is essential in preventing in vivo transmission of HTLV-1 to human T cells in NOD-SCID/¿cnull (NOG) mice

Abstract: Background: Human T-cell leukemia virus type 1 (HTLV-1) causes both neoplastic and inflammatory diseases, including adult T-cell leukemia and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Because these life-threatening and disabling diseases are not yet curable, it is important to prevent new HTLV-1 infections.Findings: In this study, we have established a simple humanized mouse model of HTLV-1 infection for evaluating prophylactic and therapeutic interventions. In this model, HTLV-1-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However, a recent study demonstrated that human T cells could be efficiently engrafted by direct transplantation of human PBMCs into the spleen of irradiated NOD/SCID/c c -/mice, creating an animal model for studying primary human T cell leukemia virus type-1 (HTLV-1) infection in vivo. 14 Interestingly, reconstitution of human T cells was barely detectable in any of the NSG mice early (2 weeks) after intraperitoneal injection of human PBMCs (Fig. 1B).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, a recent study demonstrated that human T cells could be efficiently engrafted by direct transplantation of human PBMCs into the spleen of irradiated NOD/SCID/c c -/mice, creating an animal model for studying primary human T cell leukemia virus type-1 (HTLV-1) infection in vivo. 14 Interestingly, reconstitution of human T cells was barely detectable in any of the NSG mice early (2 weeks) after intraperitoneal injection of human PBMCs (Fig. 1B).…”
Section: Discussionmentioning
confidence: 93%
“…Although the upgraded nonobese diabetic (NOD/SCID) mouse has led to improved human cell engraftment, the percentage of engrafted human cells following intraperitoneal injection has remained suboptimal and highly variable. [6][7][8][9][10] NOD/SCID mice harboring either a null allele at the b 2microglobulin locus (NOD/SCID/b2m -/-) 11 or a truncated common cytokine receptor c chain (cc) mutant lacking its cytoplasmic region (NOD/SCID/c c -/-) [12][13][14] were developed as model animals. In these mice, natural killer (NK) cells as well as T and B cells are disrupted because b2m is necessary for major histocompatibility complex (MHC) class I-mediated innate immunity and cc (IL-2Rc chain) is an indispensable component of receptor heterodimers for many lymphoidrelated cytokines, such as interleukin (IL)-2, IL-7, IL-9, IL-12, IL-15, and IL-21.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we tested the protective efficacy of hu-LAT-27 mAbs against in vivo infection with HTLV-I using our humanized mouse model as reported previously [ 18 ]. PBMCs from HTLV-I-negative donors were transplanted directly into the spleen of NOG mice together with the mitomycin-C-treated HTLV-I-producing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, LAT-27 reacted all HTLV-I-producing cell lines tested, including naturally infected cell lines from ATL and HAM/TSP patients and asymptomatic carriers. So far, the potential of passive immunization with IgG from HTLV-I carriers has been show in rabbit [ 25 , 26 ], monkey [ 27 ] and humanized NOG mouse models [ 18 ]. Since polyclonal antibodies contain non-neutralizing antibodies, the efficacy of neutralization by neutralizing antibody could be interfered with by those non-neutralizing anti-gp46 antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation